Hannah Arendt and the history of thought - Brennan, Daniel HerausgeberIn; La Caze, Marguerite HerausgeberIn (Continental philosophy and the history of thought, 2022)
Paul Dahlgren, "the course of true love" : Arendt's Shakespeare, love, and the practice of storytelling -- Matthew Wester, Jaspers, Kant, and the origin of Hannah Arendt's theory of judgment -- Kimberley Maslin, Hannah Arendt and early German romanticism -- Maria Tamboukou, the gendered politics of love : an Arendtian reading -- Liesbeth Schoonheim, Arendt and Beauvoir on romantic love -- Eric Stephane Pommier, Arendt and Hans Jonas : acting and thinking after Heidegger -- Katarzyna Stokłosa, Hannah Arendt's influence on Eastern European dissidence : the example of Poland -- Laura Mcmahon, the phenomenological sense of Hannah Arendt : plurality, modernity, and political action -- Marieke Borren, Arendt's phenomenologically informed political thinking : a proto-normative account of human worldliness -- Andrew Schaap, denaturalizing Hannah Arendt and Claudia Jones : statelessness, citizenship and racialization -- Joel Rosenberg, the life of the unruly in Ada Ushpiz's Vita activa: the spirit of Hannah Arendt (2016).